2022
DOI: 10.1101/2022.06.09.495451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Oxygen Plasma Treatment on Parylene C and Parylene N Membrane Biocompatibility for Tissue Barrier Models

Abstract: Porous membranes are integral components of in vitro tissue barrier and co-culture models and their interaction with cells and tissues directly affects the performance and credibility of these models. Plasma-treated Parylene C and Parylene N are two biocompatible Parylene variants with perceived potential for use in these models but their biocompatibility and biological interactions at their interface with cells are not well understood. Here, we use a simple approach for benchtop oxygen plasma treatment and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Their biocompatibility, how to certify it, and the processing requirements have been presented in the literature [ 45 ]. Medical grade resins have been employed in cadavers for pelvic tumor resection [ 46 ], for bone fixation in femoral fractures in orthopedics [ 47 ], in surgical instruments [ 48 ], in face anatomy for the fabrication of face masks [ 49 ], in health monitoring devices [ 50 ], in tracheal grafts [ 51 ], in implantable vaccines [ 52 ], in tissues [ 53 ], in bio-microfluidic devices [ 54 ], in oncological orthopedics [ 55 ], in medical inhalers [ 56 ], and in eye treatments [ 57 ]. Nanocomposites have been developed to enhance the mechanical performance of medical-grade resins [ 58 ] and to induce antibacterial properties [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their biocompatibility, how to certify it, and the processing requirements have been presented in the literature [ 45 ]. Medical grade resins have been employed in cadavers for pelvic tumor resection [ 46 ], for bone fixation in femoral fractures in orthopedics [ 47 ], in surgical instruments [ 48 ], in face anatomy for the fabrication of face masks [ 49 ], in health monitoring devices [ 50 ], in tracheal grafts [ 51 ], in implantable vaccines [ 52 ], in tissues [ 53 ], in bio-microfluidic devices [ 54 ], in oncological orthopedics [ 55 ], in medical inhalers [ 56 ], and in eye treatments [ 57 ]. Nanocomposites have been developed to enhance the mechanical performance of medical-grade resins [ 58 ] and to induce antibacterial properties [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few reports have shown that coating resin 3D printed materials with parylene-C increased their compatibility with cell lines in direct or indirect contact with the materials. [13][14][15][16] Parylene derivatives are a trusted material used for coating neural or cardiovascular implants and stents, 17 as well as a substrate for microscale cultures. 18,19 Parylene-C is the most affordable and commonly used derivative of the para-xylylene polymers and is conformally applied via vaporization.…”
mentioning
confidence: 99%